Saberes y prácticas de los adolescentes escolares en situación de obesidad: implicancias para la enfermería - Nájera Gutiérrez, Gudelia (2016)
Qualitative research which had the aim of study the knowledge and practices of school adolescents in situation of obesity. The theoretical approach was based on the theory of Paulo Freire's knowledge of education, Foucault, knowledge of reality, Le Breton the knowledge of the body and Waldow human care. It is based on the explanatory method, depth interview technique, and participant observation was used to meet the knowledge and practices made by students who have obesity and collect the data. From the interviews were conducted up to the saturation of information. The population consisted of seven students of basic level, with a diagnosis of obesity, for the analysis of the information analysis of thematic content of Minayo (2012) is worked. The results emerge two categories the first: Common Knowledge (in) the adolescent and family. The second category: The body and the teen has two attributes: body image and the other's gaze. The final considerations point out that according to the first category the family remains an important element for the adolescent to acquire knowledge about obesity, which despite having some obesity-related knowledge has not become aware of the damage that can cause their health and make health care practices and food, exercise to reduce this problem. And on the second category we realize how important it is to the body, as it is at the stage where the physical body is the most important, where it is in a society that is school, marking the accept at that society and if they do not accept their physical then this means that he is not comfortable with your body and see it as something bad, like their peers.